Exclusive Breastfeeding Knowledge, Practice, and Perceived Challenges Among In-School Adolescent Mothers in Dodoma Region, Tanzania. - Millanzi, Walter C.; Shaha, Maulid K. (Child & Adolescent Social Work Journal, 2026)
Exclusive breastfeeding (EBF) is a critical public health practice that significantly improves maternal and newborn health outcomes. However, the prevalence of EBF among adolescent mothers remains disproportionately low, particularly in developing countries, including Tanzania. This study aimed to assess the EBF knowledge and practices, as well as the perceived EBF challenges, among adolescent mothers in the Dodoma region, Tanzania. An analytical cross-sectional study was conducted with a sample of 193 adolescent mothers from both government and private schools in the Dodoma region. Data were collected through structured questionnaires adapted from previous studies. Descriptive statistics were used to analyze proportions and distributions using the IBM Statistical Package for Social Sciences (SPSS) computer software program version 26. Moreover, multivariate regression analysis was employed to identify factors associated with EBF knowledge and practices set at a 95% confidence interval (CI) and 5% (p < 0.05) significance level. The average age of adolescent mothers was 14 years with a standard deviation of 0.325, and 91.7% (n = 177/193) of them attended government schools. The study revealed a low level of knowledge (64.2%) and low practice (82.9%) regarding EBF among adolescent mothers. Commonly reported challenges included a lack of breastfeeding space at schools (40.9%), poverty (33.7%), breast pain (32.1%), and cultural beliefs that breast milk is insufficient for newborns (76.2%). However, adolescents from urban areas were twice as likely to have higher EBF knowledge (β = 2.325; 95%CI: 1.282–5.2741; p = 0.014) and more likely to engage in better EBF practices (β = 1.366; 95%CI: 1.015–4.253; p = 0.036) compared to those from rural areas. Ownership of a mobile phone (β = 1.832; 95%CI: 1.043–4.205; p = 0.035) and participation in online social media platforms (β = 2.439; 95%CI: 1.437–5.731; p = 0.023) were associated with higher EBF knowledge and practices, respectively. Adolescent mothers in the Dodoma region face significant and complex challenges that impede their ability to exclusively breastfeed their children. The findings emphasize a critical need for targeted and culturally appropriate interventions that utilize modern media platforms for education and address key social, structural, and cultural barriers. Policymakers, teachers, health practitioners, and other stakeholders should focus on creating supportive environments within schools, health facilities, and communities to enhance EBF knowledge and practices, ultimately leading to improved health outcomes for both mothers and infants.